PENYESUAIAN BESARNYA PTKP BERDASARKAN PMK-162/PMK.011/2012 ATAS PMK-252/PMK.03/2008 TENTANG PAJAK ATAS PENGHASILAN SEHUBUNGAN DENGAN PEKERJAAN ORANG PRIBADI ( KAJIAN UNTUK PEGAWAI TETAP) - Yulita Setiawanta (MEDIA, 2012)
This research-based review of the literature by using Article 7:Â  Act No.. 36 of 2008 on the exemption in respect of income tax that is operationally Personal translated through PMK-252/PMK.03/2008 (effective from January 1, 2009) concerning guidelines on income tax withholding with respect to employment, services, and activities People PMK-162/PMK.011/2012 personal with (effective from October 22, 2012 (provisions on adjusting the amount of income exempt from tax came into effect on January 1, 2013). diskritif Comparative Methods used by the literature to explain or elaborate on the case approach each tax regulation is then contrasting. Objects used are fictitious or imaginary taxpayer. Results of this study indicate that, it is necessary to adjust the latest tax regulations relating to the calculation of the income tax article 21 permanent employees.